Strategi Optimalisasi Digital Marketing Sebagai Media Pemasaran Pada Bisnis Bakery - Taradiva Adisty; Rusdi Hidayat Nugroho (Jurnal Pengabdian Masyarakat, 2023)
Marketing has a fairly large role in life because marketing deals with various aspects, especially in the economic field. Digital marketing is a way for someone to market their business products via the internet. The purpose of this activity is to carry out digital marketing optimization strategy with one of the MSMEs in Cerme Kidul Village, Gresik Regency, namely Sweety Bakery. Sweety Bakery is a business engaged in the retail sector by selling several types of bread and cakes including eclairs, donuts, sweet breads and tarts. The method used in this activity is interviews, literature studies, and direct assistance activities. Data analysis performed using SWOT analysis and IE Matrix. The results from this study are to find out the formulation alternative marketing development strategies for UMKM Sweety Bakery, (1) Maintaining product prices and quality to strengthen good relations with consumers, (2) Maintaining product prices and quality by increasing innovation in products according to patterns public interest, (3) Increasing optimal product marketing to increase bakery business opportunities in Gresik Regency, (4) Increasing optimal product marketing so that it can compete with competitors who are already using digital marketing. The activity of implementing digital marketing as a marketing strategy for Sweety Bakery has also succeeded in improving the quality of content publication which can increase the number of impressions from several social media accounts that Sweety Bakery already has.